PENINGKATAN KINERJA PERUSAHAAN MELALUI IMPLEMENTASI SISTEM ENTERPRISE RESOURCE PLANNING DAN SUPPLY CHAIN MANAGEMENT - A SYSTEMATIC LITERATURE REVIEW - Fahrezi, Moh. Nanda Putra; Dewayanto, Totok (Diponegoro Journal of Accounting, 2024)
This study discusses the implementation of Enterprise Resource Planning (ERP) and Supply Chain Management (SCM) systems and their impact on improving company performance. A systematic literature review of articles indexed in SCOPUS was utilized to analyze and synthesize findings related to the topic. The research demonstrates that the implementation of ERP and SCM systems holds significant potential for enhancing company performance. However, the primary challenge lies in addressing critical factors that influence the success of the implementation, such as user satisfaction, complexity, training, user engagement, management support, and compatibility. User satisfaction is considered the most crucial factor in ERP and SCM implementation. If users feel content with the system's usability, they will be more motivated to maximize its benefits in their daily work. Additionally, complexity needs to be carefully addressed and can be overcome through adequate training, active user engagement, and strong top management support. The implementation of ERP and SCM systems positively impacts company performance through increased operational efficiency, cost reduction, faster response times, and improved customer satisfaction. However, the sustainability of system usage also requires attention, particularly concerning factors such as user engagement, continuous training, and periodic evaluations. This research provides a comprehensive understanding of the relationship between ERP and SCM implementation and the enhancement of company performance. The practical implication of this study is that organizations must pay attention to critical factors influencing implementation and ensure that system usage is effectively managed within their business context. Although this research contributes significantly to the understanding of ERP and SCM implementation, there are limitations related to the number of literature sources used, resulting in less variation in the findings. Therefore, further research is needed, involving a broader analysis of literature, to enrich the understanding of ERP and SCM system implementation and its impact on improving company performance.